Faktor-Faktor Yang Berhubungan Dengan Kejadian Persalinan Prematur Di RSUD Cibinong - Nurul Syuhfal Ningsih (Politeknik Karya Husada, 2022)
Background: The number of premature infant deaths in hospitals in 2014 was 169 cases. The number of premature infant deaths in 2015 increased by 180. Purpose : To find out the factors related to the incidence of preterm delivery in Cibinong Hospital, Bogor Regency. Method: This research is correlative analytic with cross sectional approach, using secondary data. This study was conducted in September 2021. The population in this study were 50 mothers who gave birth prematurely. The dependent variable was preterm delivery and the independent variables were age, birth spacing, infection, parity, education and ANC visits. The analysis used is univariate and bivariate. The results of the bivariate analysis were obtained, age p-value = 0.019 birth spacing p-value = 0.293 infection p-value = 1,000 parity p-value = 0.001 education p-value = 0.498 ANC visits p-value = 0.085 with the incidence of preterm labor at Cibinong Hospital . Result: The results of the bivariate analysis showed that the age variable had a relationship with the incidence of preterm labor with p-value = 0.019 OR=4.737 (0.904-24,809%), and the parity variable had a relationship with the incidence of preterm delivery with p-value = 0.001 OR=1.161 (0.208- 6,473). Conclusion: There is a relationship between age and preterm labor and parity with preterm labor. With this research, it is hoped that mothers with preterm labor can reduce.